The southernmost occurrence of Brachycarcharias (Lamniformes, Odontaspididae) from the Eocene of Antarctica provides new information about the paleobiogeography and paleobiology of Paleogene sand tiger sharks - Marrama, Giusppe (2018)
The first record of one of the most common and widespread Paleogene selachians, the sandtiger shark Brachycarcharias, in the Ypresian strata of the La Meseta Formation, Seymour Island, Antarctica, is providedherein. Selachians from the early Eocene horizons of this deposit represent the southernmost Paleogeneoccurrences in the fossil record, and are represented by isolated teeth belonging to orectolobiforms, lamniforms,carcharhiniforms, squatiniforms and pristiophoriforms. The combination of dental characters of the 49 isolatedteeth collected from the horizons TELMs 2, 4 and 5 supports their assignment to the odontaspidid Brachycarchariaslerichei (Casier, 1946), a lamniform species widely spread across the Northern Hemisphere during the early Paleogene.The unambiguous first report of this lamniform shark in the Southern Hemisphere in the Eocene of the LaMeseta Formation improves our knowledge concerning the diversity and paleobiology of the cartilaginous fishesof this deposit, and provides new insights about the biotic turnovers that involved the high trophic levels of themarine settings after the end-Cretaceous extinction and before the establishment of the modern marine ecosystems.